DIGITAL PRESENCE OF COMPANIES IN THE VENTILATION MARKET OF UKRAINE: COMPARATIVE ANALYSIS OF WEBSITES, SOCIAL MEDIA AND BRAND BOOKS - KARPENKO, Vitalii; BILYK, Artem; GYMENUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a thorough study of the digital presence of companies operating in the field of ventilation and air conditioning equipment in Ukraine. The official websites, social media pages (Facebook, Instagram, YouTube, LinkedIn) and the presence and content of brand books of leading market participants were analyzed. Particular attention was paid to the quality of design, usability, SEO optimization, content richness, style and visual identity, as well as correspondence between different digital channels. A detailed comparative analysis of the digital strategy of leading companies operating in the field of ventilation and climate equipment was conducted, namely LLC "Scientific and Production Center of Ventilation and Air Conditioning", VENTS, PRANA and ECO-LIFE. The main criteria were: quality and functionality of official websites, activity and effectiveness of communication in social networks, presence and level of development of the brand book, consistency of visual identity on various digital platforms. As a result, market leaders were identified that demonstrate high indicators of digital presence, in particular due to modern design, convenient navigation, high-quality content and active interaction with the audience. A number of shortcomings were identified among other market participants, such as the use of outdated design solutions, the lack of adaptive mobile versions of sites, the presence of irrelevant or long-unupdated content, a low level of user engagement in social networks, as well as insufficient consistency and integrity in the application of brand style in various communication channels. By eliminating these shortcomings, you can increase their competitiveness in today’s market conditions. Prospects for further research include expanding the number of analyzed companies, studying the impact of digital tools on sales performance and the formation of reputational capital of brands in the field of ventilation.